성인 남자 주의력결핍 과잉행동장애 환자에서 인터넷 중독 성향에 관여하는 특성 - 노동현; 김준원; 민경준; 이영식; 김붕년; 정재훈; 안지영; 한덕현 (Singyŏng chŏngsin ŭihak, 2014)
Objectives This study was conducted in order to investigate characteristics of temperament, depression, anxiety, attention, and impulsivity in adult males with Attention Deficit/Hyperactivity Disorder (ADHD) and internet addiction tendency. Methods The survey participants were 181 (121 patients and 60 healthy control subjects) adult males older than 19 years of age in Chung-Ang University Hospital and Gongju National Hospital. Subjects were divided according to ADHD with internet addiction tendency (AI), pure adults with ADHD (AD), and healthy control subjects (HC). All groups completed the Adult ADHD Scale (AADHD), Wender-Utah ADHD Rating Scale (WUADHD), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), the Korean Version of Young Internet Addiction Scale (YIAS-K), Barratt Impulsiveness Scale (BIS) and Temperament Character Inventory-Revised Short version for identification of relationship between ADHD and internet addiction tendency. Results AI groups were found to have higher AADHD, WUADHD, BDI, YIAS-K, and Novelty Seeking scores, compared to the AD and HC groups. The Cooperativeness score of the AI group was significantly lower than that of the AD group and HC group. The BAI and BIS scores of the AI group and AD group were significantly higher than those of the HC group. The Self-Directedness scores of the AI group and AD group were decreased, compared to the HC group. YIAS-K scores were partially related to BDI scores in the AI group. Conclusion The results of this study indicate an association of higher score of BDI with internet addiction tendency in adult patients with ADHD. Management of temperament characteristics, depression, anxiety, attention, and impulsivity may be important for adults with ADHD and internet addiction tendency. KCI Citation Count: 2